Incident portal vein thrombosis in liver transplant recipients in New Zealand: Predictors of risk and validation of portal vein thrombosis risk index calculator - Garg, Paras; Harrison, Barry; Gane, Edward J. (Frontiers in Transplantation, 2022)
Spontaneous portal vein thrombosis(PVT) risk is increased in patients on waiting list for liver transplant and increases perioperative risks. A predictive PVT risk-index(PVT-RI) calculator has been proposed to determine risk of incident PVT. We performed retrospective analysis on adult liver transplant recipients at NZ Liver Transplant Unit between January 1998 and February 2020. Variables reviewed included age at listing and transplantation, wait time from listing to transplant, indication for listing, gender, ethnicity, aetiology of liver disease, listing MELD score, hepatocellular carcinoma(HCC), moderate-to-severe ascites, hepatic encephalopathy(>grade 2), transjugular intrahepatic portosystemic shunt(TIPSS), spontaneous bacterial peritonitis(SBP), and diabetes. Incident PVT was determined by imaging on waiting list and assessment at transplantation. 553 out of 706 patients met inclusion criteria. 18 out of 553(3.3%) patients had incident PVT. The PVT-RI calculator was not validated in our cohort with only 1/18(6%) patient with PVT scoring >4.6 (high risk cut-off score). Longer waiting time for transplant and listing for liver failure rather than HCC were independent predictors of incident PVT risk. There was no statistically significant difference for incident PVT in viral vs non-viral and cholestatic vs non-cholestatic aetiology of chronic liver disease. Patients with longer waiting times on transplant waiting list should be monitored regularly for PVT.